Seismic dataset in the the Gulf of Porto Ercole, Tuscany, Italy (Hisope project) - Alessandro Conforti; Gilles Brocard (PANGAEA, 2024)
The seismic data acquisition shown in the repository was done in the frame of the HISOPE project, which is intended to provide critical marine geological and archaeological constraints, in support of two currently funded coastal research projects: the IDEX Lyon project Thalassocracies without a port, myth or reality? (2020-2022) and the LabEx-IMU (Institut des Mondes Urbains) URBO project (2020-2023). These projects are carried by the Archéorient laboratory (UMR 5133 CNRS - Université Lyon 2) as part of a scientific consortium associating several other French and Italian laboratories and institutions: UMR 5189 HiSoMA, UMR 5600 EVS (ENS Lyon - Univ. Lyon 1 ), the Italian archaeological superintendencies of Lazio and Tuscany, the Museo civico del mare e della navigazione antica de Santa Severa, the University of Florence, the University of Roma-La Sapienza, the CNR, the WWF, the Municipality of Orbetello. The main objective is to discover ancient port cities along the seafront of the Tyrrhenian Sea. If the Roman ports, dating from the 4th century BC were discovered, the Etruscan ports (dating from the 10th to the 5th century BC) remain untraceable. The Etruscans are one of the only Mediterranean thalassocracies (societies based on maritime commercial and military power) whose archaeologists have never found the ports. The second objective is to determine the environmental characteristics of the sites chosen for the foundation of the Etruscan ports. The study of the evolution of these environments will also make it possible to understand the factors (environmental, political, economic) which led to their disappearance, and to the ex nihilo creation of new port sites in Hellenistic and Roman times. These projects are based on a resolutely interdisciplinary approach and bring together historians, archaeologists, geophysicists, geologists and geoarchaeologists. The main goals of the field campaigns carried out in this context are 1 ° to identify the location of the port basins (underground or at sea), and 2 ° to sample the study sites, in order to characterize their geological environment. For these reasons, the field missions combine terrestrial geophysical prospecting as well as terrestrial coring campaigns and lagoon coring. The main archaeological targets of the 2019 and 2020 campaigns were two Etruscan coastal cities: Pyrgi (Lazio) and Orbetello (Tuscany). In both cases, land surveys (geophysical and coring) have shown that, contrary to the dominant hypotheses, the port basins are not currently located on land. The present HISOPE - IFREMER project therefore aims to use sediment imagery to determine if they are present at sea, and to characterize the evolution of the coastline that has led to this present state. The reasons are very different in each case. In Pyrgi, the coastline has receded sharply since Etruscan times, due to rapid beach erosion. This decline sharply accelerated in the 20th century, threatening this important archaeological site. In Orbetello, the lagoon, in which the ancient city was settled, seems to have become a more restrictive environment over time; even becoming a source of countless environmental problems, against which the inhabitants still struggle today. The present HISOPE - IFREMER project aims to acquire high frequency seismic lines on these two sites. At Pyrgi, in an open sandy marine environment, sediment imagery will help determine the position of ancient shorelines, and determine the ancient positioning of archaeological remains discovered 350 m offshore, in October 2020. In Orbetello, set of measurements, in front of a tombolo that closes the lagoon, aims to document the source of a high-energy event that affected the lagoon after Roman times. In addition to providing answers to archaeologists, these measurements will provide fundamental information on the dynamics of these environments, making it possible to improve the fight against coastal erosion in Pyrgi, and the fight against the progressive confinement of the lagoon in Orbetello. Seismic data were acquired with high resolution 3,5 kHz Ixblue Subbottom Profiler, customized by Ifremer institute to optimize the data acquisition in shallow water; the sonar was hull mounted on board of the Haliotis research vessel; data post processing was performed by QC_Subop software (developed by Ifremer /REM/GEOOCEAN/ANTIPOD laboratories), and Geosuite software (license to CNR of Oristano). The flow processing was based on signal normalization, basic band pass filtering, and gain adjustment by Liner Gain (LG) or Time Varying Gain (TVG), depending on acquisition depth and sea bottom reflectivity . In the repository are provided navigation data (shape and Kmz file) showing navigation points; let extquotesingles find in the attributes the file and line name, the progressive fix number of each profile (related to the acquisition shot) and the acquisition date (Year, month, day, hour. Minute, second); processed profiles are shown in jpg files with reference to line name, fix/shot (for horizontal scaling) and vertical scale in milliseconds; a conversion table from ms to meters is provided in the repository, assuming 1500 as sound velocity speed in the water.